Periodic solutions for fourth‐order nonlinear functional difference equations. (12th December 2013) - Liu, Xia; Zhang, Yuanbiao; Shi, Haiping; Deng, Xiaoqing
<x xml:space="preserve">Abstract</x> By using the critical point method, some new criteria are obtained for the existence and multiplicity of periodic solutions for fourth‐order nonlinear functional difference equations. The proof is based on the linking theorem in combination with variational technique. Recent results in the literature are generalized and significantly improved. Copyright © 2013 John Wiley & Sons, Ltd.